Cued Fear Conditioning in Carioca High- and Low-Conditioned Freezing Rats - Macêdo-Souza, Carolina; Maisonnette, Silvia S.; Filgueiras, Claudio C.; Landeira-Fernandez, J.; Krahe, Thomas E. (Frontiers in Behavioral Neuroscience, 2020)
Anxiety disorders comprise a broad range of psychiatric conditions, including general anxiety (GAD) and specific phobias. For the last decades, the use of animal models of anxiety has offered important insights into the understanding of the association between these psychopathologies. Here we investigate whether Carioca high and low conditioned freezing rats (CHF and CLF, respectively), a GAD animal model of anxiety, show similar high and low freezing behavioral phenotypes for cued auditory fear conditioning. Adult CHF (n = 16), CLF (n = 16) and normal age-matched Wistar rats (control, CTL) were tested in a classical auditory-cued fear conditioning paradigm over 3 days. Freezing responses were measured and used as evidence of fear conditioning. Overall, both CHF and CLF rats, as well as CTL animals, displayed fear conditioning to the auditory CS. However, CLF animals showed a rapid extinction to the auditory conditioned stimulus compared to CHF and CTL rats. We discuss these findings in the context of the behavioral and neuronal differences observed in rodent lines of high and low anxiety traits.